Comparative analysis of genetic landscape of carbapenem-resistant Acinetobacter baumannii in India: A computational whole-genome study - Rhythm Sharma; Dinesh Lakhanpal (The Microbe)
Acinetobacter baumannii is a Gram-negative, aerobic bacterium responsible for multidrug-resistant nosocomial infections, especially in Intensive Care Units. This study investigated the genetic diversity, antimicrobial genes, virulence factors, and mobile genetic elements, resistance genes in clinically relevant strains of A. baumannii circulating in the Indian population, consistent with reports from other Asian countries, including China, Southeast Asia, and Thailand. A comprehensive analysis of carbapenem-resistant A. baumannii strains was conducted using publicly available genomic data. Pan-genome fanalysis revealed an open genome structure, indicating the pathogen's potential for ongoing genetic evolution. The study identified significant resistance genes, including blaOXA-23, AdeIJK and AdeFGH type efflux pumps, and carbapenemases. Virulence factors such as OmpA, phospholipase, and Csu pili were prevalent, contributing to the bacterium's pathogenicity. Mobile genetic elements, including Tn2006 and ISAba1/blaOXA-23 gene combinations, were also identified, highlighting the mechanisms behind the rapid spread of resistance genes. Subtractive proteomics was employed to identify core proteins essential to the bacterium but non-homologous to humans, highlighting them as potential drug targets. This analysis identified 2165 core proteins, with 550 non-homologous essential proteins located in the cytoplasm. Further evaluation of these proteins based on stability and involvement in essential pathways, we identified 15 druggable proteins as potential targets for antimicrobial agents. The findings underscore the critical need for continuous surveillance, innovative drug development, and targeted therapeutic strategies to mitigate the impact of multidrug-resistant A. baumannii in healthcare settings. Addressing antimicrobial resistance in A. baumannii remains a global health priority, especially in high-burden regions like India, where the prevalence of resistant strains is notably high. This study provides a foundation for future research and development in combating this formidable pathogen.